Representing, re-presenting, or producing the past? memory work amongst museum employees - Aroles, Jeremy; Morrell, Kevin; Granter, Edward; Liang, Yin (Wiley, 2026)
Though it is widely understood that the past can be an important resource for organizations, less is known about the micro-level skills and choices that help to materialize different representations of the past. We understand these micro-level skills and choices as a practice: ‘memory work’ – a banner term gathering various activities that provide the scaffolding for a shared past. Seeking to learn from a context where memory work is central, we share insights from a quasi-longitudinal study of UK museum employees. We theorize three ideal-typic regimes of memory work, namely representing, re-presenting and producing the past, and detail the micro-practices through which these regimes are enacted. Through explaining the key features of memory work in this context, our paper offers novel, broader insights into the relationship between occupations and memory work, showing how occupations differ in their understanding of memory and how this shapes their memory work.
Special Issue: Occupations and Memory in Organization Studies
Keywords: memory work; museums; occupations; past